Rubus tetsunii, a replacement name for the Chinese R. lobatus T. T. Yu & L. T. Lu (Rosaceae) - Wang, Huanchong; Sun, Hang (Phytotaxa, 2013)
Rubus Linnaeus (1753: 492), consisting of approximately 700 species, is one of the largest genera in the Rosaceae and is found in all continents except Antarctica (Lu & Boufford 2003). The genus Rubus is a taxonomically notoriously complex one, and species circumscription is complicated by hybridization, polyploidy, agamospermy, and lack of a universal species concept (Weber 1996).